A comparative study of atorvastatin and rosuvastatin on lipid lowering efficacy in hyperlipidemic patients - Tonu, Samia Haque; Dewan, Zesmin Fauzia; Akhter, Nargis; Banerjee, Sajal Krishna (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The aim of the present study was to compare the lipid lowering effect of atorvastatin and rosuvastatin in patients (n=52) with hyperlipidemia. Patients were assigned to atorvastatin 10 mg or rosuvastatin 5 mg daily for 8 weeks. The blood was collected at baseline and after intervention to measure the serum lipid profile. The level of serum total cholesterol in both atorvastatin and rosuvastatin groups was significantly reduced after intervention (p<0.00001 and p<0.00001 respectively) but no statistically significant difference (p=0.503) was observed between the two statin-treated groups. The reduction of serum triglyceride level was also significant (p=0.046 in atorvastatin group and p=0.0006 in rosuvastatin group). No significant difference was observed between the two groups (p=0.312). The serum LDL-C level was reduced significantly in both atorvastatin group (p<0.00001) and rosuvastatin group (p<0.00001). Again no statistically significant difference (p=0.749) was observed between the two groups. No significant change was observed in the serum HDL level. Intergroup difference was not significant (p=0.721). The present study indicates that both atorvastatin and rosuvastatin improve the lipid profile but no significant change was observed between the two groups.